Pengaruh Latihan Lateral Barrier Hop Terhadap Kecepatan Tendangan pada Atlet Pencak Silat usia 11-15 tahun di PSHT Cabang Jakarta Selatan Tahun 2024 - Viecilia Tirta Buana Imron; Yulis Susanti; Ezra Bernardus Wijaya (JOURNAL SAINS STUDENT RESEARCH, 2024)
With high speed, kicks have the potential to be more effective in damaging or hitting an opponent. In pencak silat, when a kick moves slowly, the opponent has more time to respond and anticipate the attack thereby increasing the opponent's chances of dodging or even meeting the kick with effective defensive techniques. The aim of this research is to determine the effect of plyometric training in the form of Lateral Barrier Hop on increasing kicking speed in Pencak Silat athletes. The research design is oneugroup pre-test and post-test with a quantitative experimental type with a research sample of 12 respondents selected using a purposive sampling method. Kick speed is measured using the Frequency Speed of Kick Test. This research proves that there is a change in T-kick speed, if seen from the pre-test average of 10.92, while the post-test gets an average value of 15.33, so the difference in average value is 4.41, P < 0.05. Plyometric movements involve jumping sideways over obstacles placed between two points which can stimulate a fast neurological response in the muscles, so that the muscles can contract more quickly and strongly, resulting in a faster kick. Lateral Barrier Hop Training can be an option to increase kick speed in pencak silat.